2020
DOI: 10.1089/can.2019.0079
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in the Management of Acute Pain: A Systematic Review and Meta-analysis

Abstract: Objective: To synthesize the best evidence surrounding the efficacy of cannabinoids for acute pain in the clinical setting based on subjective pain scores and observed adverse effects. Design: Systematic review with meta-analysis. Data Sources: PubMed, Embase, Cochrane Databases, and Google Scholar. Eligibility Criteria: English-language randomized-controlled clinical trials comparing cannabinoids with placebo in patients with acute pain. Data Extraction and Synthesis: Study quality was assessed using the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…Selecting studies focused on acute pain, Gazendam has analysed six oral administration trials, mainly, of THC. This analysis revealed that there was a small, but significant, reduction in subjective pain scores compared with placebo in patients experiencing acute pain [ 274 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selecting studies focused on acute pain, Gazendam has analysed six oral administration trials, mainly, of THC. This analysis revealed that there was a small, but significant, reduction in subjective pain scores compared with placebo in patients experiencing acute pain [ 274 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence of the effectiveness of cannabinoids for acute pain states is poor 11. This is partially due to lack of satisfactory studies rather than a surfeit of negative studies.…”
Section: Limitations Of Current Cannabis and Pain Researchmentioning
confidence: 99%
“…The role of central CB1R, and both central and peripheral CB2R inducing anti-nociceptive actions in neuropathic and inflammatory models of pain has been described in earlier ( Section 3.2.2 and Section 3.2.3 ). Additionally, recently conducted retrospective and meta-analysis revealed the utility of cannabinoids in the treatment of postoperative pain and other forms of acute pain states [ 589 , 590 ]. Interestingly, the peripheral CB1R has also been implicated in inducing anti-nociception and resolving associated inflammatory states in various animal models of pain [ 591 , 592 , 593 , 594 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%